Suppression of Tumorigenicity in Breast Cancer Cells by the Microfilament Protein Profilin 1 - Janke, Jürgen (The Rockefeller University Press, 2000)
Differential display screening was used to reveal differential gene expression between the tumorigenic breast cancer cell line CAL51 and nontumorigenic microcell hybrids obtained after transfer of human chromosome 17 into CAL51. The human profilin 1 (PFN1) gene was found overexpressed in the microcell hybrid clones compared with the parental line, which displayed a low profilin 1 level. A comparison between several different tumorigenic breast cancer cell lines with nontumorigenic lines showed consistently lower profilin 1 levels in the tumor cells. Transfection of PFN1 cDNA into CAL51 cells raised the profilin 1 level, had a prominent effect on cell growth, cytoskeletal organization and spreading, and suppressed tumorigenicity of the stable, PFN1-overexpressing cell clones in nude mice. Immunohistochemical analysis revealed intermediate and low levels of profilin 1 in different human breast cancers. These results suggest profilin 1 as a suppressor of the tumorigenic phenotype of breast cancer cells.